Effect of Split‐File Digital Workflow on Crown Margin Adaptation. Issue 7 (9th June 2017) - Sheridan, Ryan R.; Verrett, Ronald; Haney, Stephan; Schoolfield, John
Abstract: Purpose: Computer‐aided design/computer‐aided manufacturing (CAD/CAM) is becoming increasingly integrated into dental practice workflow at a pace that exceeds scientific validation. The aim of this study is to evaluate a complete digital split‐file protocol relative to segmental digital and analog techniques for restoring a single maxillary anterior edentulous space with custom abutment and crown. Materials and Methods: Four treatment workflows were assessed: complete digital (CD), segmental digital (SD), milled wax (AM), and heat pressed and hand waxed (AH) and heat pressed. The CD workflow "split" an abutment and crown into separate files to fabricate a zirconia abutment and both zirconia/lithium disilicate crown restorations. The SD workflow scanned the existing abutment for design of segmental restorations in zirconia, lithium disilicate, and milled wax (AM). The AH specimens were conventionally hand waxed. Both the AM and AH specimens were heat pressed with lithium disilicate. All restorations were evaluated with standardized measurements using scanning electron microscopy (SEM) as manufactured without internal adjustments and after manual adjustment. The number of adjustments, adjustment time, and location of adjustments were recorded. One‐way ANOVA with repeated measures was used to report geometric means with 95% confidence intervals. Results: The mean marginal gap after adjustment of the CD group was 69 μm, with an upper bound (UB) of 79 μm and a lower bound (LB) of 60 μm. SD group mean was 26 μm with an UB of 31 μm and LB of 22 μm. The AM group mean was 32 μm, with an UB of 49 μm and a LB of 20 μm; AH group mean of 26 μm with an UB of 34 μm and a LB of 20 μm. The SD, AM, and AH workflows were statistically similar ( p = 1.000), and the CD workflow was statistically greater than the other three ( p < 0.001). Conclusions: The split‐file (CD) protocol results in marginal gap size within clinical standards after adjustment; however, 52 of the 60 digitally produced restorations showed a horizontal marginal offset that required adjustment for proper contours.